Global Manufacturing Growth: Role of Demand Growth and Market Share Changes - Aksoy , M. Ataman; Ng, Francis (Current Topics on Business, Economics and Finance Vol. 4, 2023)
This chapter decomposes manufacturing import growth rates in a sample of large industrial and developing countries (five industrial and eight developing) and assesses the relative contributions of domestic demand and market share changes over two distinct time periods (1991/92-2001/02 and 2001/02-2007/08). It also displays the percentages of imports from the rest of the world and developing countries for aggregate and three-digit manufacturing sectors. The authors updated their results and found the same results corroborating the greater contribution of market share changes to global trade growth. Imports from developing countries have increased much faster in both industrial and developing country markets, owing primarily to changes in market share. However, more than half of developing-country market share gains are due to Chinese exports, which account for more than 70% of developing-country market share gains in our sample countries. Despite rapid growth, developing countries' share of gross absorption in the sample countries remains very low and has the potential to grow significantly even if demand growth is much lower in the near future.